2023
DOI: 10.1038/s41433-023-02719-1
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal susceptibility profiles for fungal isolates from corneas and contact lenses in the United Kingdom

Stephen Tuft,
Neil R. H. Stone,
Matthew J. Burton
et al.

Abstract: Objective To report the identification and results of susceptibility testing for fungal isolates from the cornea or contact lens care systems. Materials and methods In this retrospective epidemiological study, we searched the results of fungal cultures from cornea or contact lens systems referred for identification and susceptibility testing to the United Kingdom National Mycology Reference Laboratory between October 2016 and March 2022. For each fungal is… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 50 publications
1
0
0
Order By: Relevance
“…In the present study, all Fusarium isolates were inhibited by the antifungal agents tested. The MIC values found are consistent with data described in studies conducted in Brazil, 15 United Kingdom, 47 Germany, 44 Netherlands, 6 Mexico, 48 India, 36,43,49 Vietnam 50 and Taiwan. 51 However, previous studies have shown variations in antifungal susceptibility among isolates of Fusarium within the same species complex.…”
Section: Discussionsupporting
confidence: 89%
“…In the present study, all Fusarium isolates were inhibited by the antifungal agents tested. The MIC values found are consistent with data described in studies conducted in Brazil, 15 United Kingdom, 47 Germany, 44 Netherlands, 6 Mexico, 48 India, 36,43,49 Vietnam 50 and Taiwan. 51 However, previous studies have shown variations in antifungal susceptibility among isolates of Fusarium within the same species complex.…”
Section: Discussionsupporting
confidence: 89%
“…A recent retrospective study from the United Kingdom evaluated the in vitro antifungal susceptibilities of 600 clinical fungal isolates. 13 95.1% of total isolates were susceptible to natamycin while 80.8% of total isolates were susceptible to voriconazole. All Fusarium organisms were susceptible to natamycin while 74.1% of Aspergillus organisms were susceptible to natamycin.…”
Section: Corneal Scraping and Culturementioning
confidence: 97%